Analysis of the “Ponte do Arco” stone masonry arch bridge - Rocco, Alex (2020)
The “Ponte do Arco” stone masonry arch bridge is located in the north of Portugal, in the municipality of Marco de Canaveses, district of Porto. The bridge is immersed in a remote natural environment and is part of the Romanesque Route, which links buildings and structures built in the area during the Romanesque Period. The “Ponte do Arco” bridge is a fine example of this type of architecture and, therefore, it deserves devoted conservation and maintenance works. The geometry of the bridge, the internal structure of the pavement and the damage state were characterised by using two non-destructive techniques, photogrammetry and ground penetrating radar, and by performing a damage survey. The data collected was used to perform limit and finite element analyses in order to estimate the structural safety level of the structure. The paper presents the structural appraisal, resulting from the non-destructive surveys and the numerical analyses.